Geometric control and modeling of genome reprogramming. Issue 4 (3rd July 2016) - Uhler, Caroline; Shivashankar, G.V.
ABSTRACT: Cell geometry is tightly coupled to gene expression patterns within the tissue microenvironment. This perspective synthesizes evidence that the 3D organization of chromosomes is a critical intermediate for geometric control of genomic programs. Using a combination of experiments and modeling we outline approaches to decipher the mechano-genomic code that governs cellular homeostasis and reprogramming.